Utilisation of dried cuttle fish (sepia officialis) waste silage in layer duck ration - Jayant Govindan (Department of Poultry Science, College of Veterinary and Animal Science, 2005)
An experiment was conducted in Department of Poultry Science, Kerala Agricultural University during the period from June to November, 2004 to assess the utilization of dried cuttle fish waste silage (CFWS) on replacement of dried fish (DF) in indigenous layer duck ration. At the age of 24 weeks, 96 layer ducks were housed under cage system of rearing with two ducks per cage. They were divided into three groups T1, T2 and T3 comprising 32 ducks per group with 8 replicates having four ducks per replicate. The three groups of ducks were fed with dietary combinations of 10 per cent DF and zero per cent dried CFWS (T1), 5 per cent DF and 11.45 per cent dried CFWS (T2) and 22.9 per cent dried CFWS replacing DF completely (T3) and the diets were made isocaloric and isonitrogenous.